The New Eden: The Influence of a Gardener and their Work, a Garden, on the Process of Climate Change - Grzelak, Eliza (Porównania, 2022)
On the 21st of May 2019 the Anthropocene Working Group has concluded that a new geological era in Earth’s history has begun—the Anthropocene. The author of the article has deduced that an interdisciplinary discourse regarding climate change should not omit human gardening activity. The Anthropocene is called an epoch of repression, short-sightedness and irreversible loss, which is shown in the work of many modern amateur gardeners. The author presents a vision of two gardens: one that has been made in a harmony of human and nature and one that is dominated solely by humans. In her article she contrasts the information from gardening guidebooks with the knowledge of amateur gardeners found in social media. The point of the article is to show the direction of modern gardening. By analysing selected texts, the author seeks an answer to the following question: are the gardeners, who see climate change, able to break out of their apathy and start to work for the environment or will they rather just continue doing what they are doing now?